1995
DOI: 10.1128/iai.63.8.3231-3234.1995
|View full text |Cite
|
Sign up to set email alerts
|

T-cell cytokine responses in human infection with Mycobacterium tuberculosis

Abstract: Compared with healthy tuberculin reactors, Mycobacterium tuberculosis-stimulated peripheral blood mononuclear cells from tuberculosis patients had diminished production and mRNA expression of the Th1 cytokines gamma interferon and interleukin 2 (IL-2), with no change in production and mRNA expression for the Th2 cytokines IL-4, IL-10, and IL-13. These results were confirmed by evaluation of T cells and CD4 ؉ cells. At the level of systemic T cells, development of tuberculosis is associated with diminished Th1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
90
2
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(108 citation statements)
references
References 21 publications
13
90
2
3
Order By: Relevance
“…When analysed for secretion of disease-associated type 2 cytokine IL-10, PBMC of healthy subjects secreted IL-10 in response to whole-cell M. tuberculosis and MT-CW but not in response to MT-CF. Similar findings were reported by Zhang et al, who demonstrated secretion of IL-10 by PBMC in response to whole-cell M. tuberculosis (Zhang et al, 1995). Because IL-10 downregulates the protective type 1 response (Turner et al, 2002), the antigens selected to design a vaccine against TB should not induce the secretion of IL-10.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…When analysed for secretion of disease-associated type 2 cytokine IL-10, PBMC of healthy subjects secreted IL-10 in response to whole-cell M. tuberculosis and MT-CW but not in response to MT-CF. Similar findings were reported by Zhang et al, who demonstrated secretion of IL-10 by PBMC in response to whole-cell M. tuberculosis (Zhang et al, 1995). Because IL-10 downregulates the protective type 1 response (Turner et al, 2002), the antigens selected to design a vaccine against TB should not induce the secretion of IL-10.…”
Section: Discussionsupporting
confidence: 86%
“…In summary, although several studies have been carried out in the past to investigate the cytokine profiles in TB patients and healthy subjects using sera and culture supernatants from PBMC and T-cell clones (Barnes et al, 1993;Zhang et al, 1995;Lin et al, 1996;Lai et al, 1997;Verbon et al, 1999), only two of these studies have followed protocols somewhat similar to ours and reported results that are consistent with our findings (Zhang et al, 1995;Lin et al, 1996). In these studies, however, only whole-cell M. tuberculosis was used as antigen to study the profiles of IFNg and IL-10 secreted by PBMC of TB patients and healthy subjects (Zhang et al, 1995;Lin et al, 1996). We, on the other hand, have studied the cytokine profiles in response to whole-cell M. tuberculosis and a wide range of other complex and single antigens of M. tuberculosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the course of successful treatment of tuberculosis patients, IgE levels appear to drop signi®cantly (Adams et al 1999). Although there is overwhelming evidence that tuberculosis itself causes transient depression of Th1 cell function, and transient enhanced Th2 phenotype cell function, some con¯icting results as regards Th2 enhancement have been reported (Zhang et al 1995) but these differences might be explained by stage and severity of tuberculosis (Dlugovitzky et al 1997) or other confounding factors that in¯uence Th1/2 balance, such as age (Shearer 1997) and nutritional state (Dai et al 1998). In tuberculoid leprosy, Th1-like cells predominate with a resistant immune response, whereas Th2-like cells are dominant in lepromatous leprosy patients with ineffective immunity (Yamamura et al 1991;Chensue et al 1994Chensue et al , 1997.…”
Section: Mycobacterial Disease Resulting From Immune Impairment Inducmentioning
confidence: 99%
“…14 A number of studies have shown that levels of IFN-g production are much lower in TB patients than in healthy controls. [15][16][17][18] Mycobacteria-infected macrophages also release large quantities of IL-6. Levels are elevated in bronchoalveolar lavage fluid of patients with active TB, and it is thought that it may play a role in multinucleated giant cell (MGC) formation from alveolar macrophages.…”
mentioning
confidence: 99%